Kalinangan construction skills training and development center - Manlutac, Margaret Gabrielle Y.; Rinen, Richard Martin E. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Being the youngest constituted barangay of Marikina City on the 10th of April in 2007, Barangay Fortune carries along with it great potential for enhancing its environment and stimulating its economic activity. The selected site is located in Barangay Fortune, zoned as a medium industrial zone with a number of residential and mixed-use buildings that promotes construction related vocational courses accredited by T.E.S.D.A., was conceptualized to stimulate the activity in the area while at the same time responding to the unending national level problems. Kalinangan: Construction Skills Training and Development Center conforms to the requirement of T.E.S.D.A. in hopes of responding to the Philippine president's (President Rodrigo Duterte) 10-Point socio-economic agenda which includes investing in human capital development, including health and education systems, and match skills & training. Some identified challenges by T.E.S.D.A. include, limited number of T.V.E.T. Institutions offering construction related qualifications, limited number of accredited trainers, assessors, and assessment centers, and lack of interest of the students to enroll on construction related programs.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman